The methodological approach to structure of management of a network of mobile communication / Pravik J. N. - Правик, Ю. Н. (Problems of Informatization and Control, 2005)
The basic tasks of system of dynamic resource management and functional characteristics of a platform of management are investigated. The arising problems are considered at operation of a network. The decisions are resulted in the field of management of malfunctions